The Nucras (Squamata: Lacertidae) of the eastern Zambezi River Basin, with the description of a new species from Zambia - Bauer, Aaron M.; Childers, Jackie L.; Burger, Marius (Zootaxa, 2025)
The Nucras of the eastern Zambezi River basin region, comprising Zambia, Malawi and central Mozambique have been poorly studied. We re-evaluated the type specimens of Lacerta cameranoi Bedriaga, 1886 and L. tessellata pseudotessellata Bedriaga, 1886, both collected at Tete, Mozambique by Wilhelm Peters in the 1840s. Both are assignable to N. ornata, the most widespread Nucras in the region. However, an additional specimen collected from Tete is referrable to N. holubi, filling a collecting gap for this species between central Zimbabwe and southern Malawi. Nucras records from northeastern Zambia include several N. boulengeri, two photo-vouchered records, one unidentifiable and the other an enigmatic form not consistent with any known species, and a new species from Senga Hill, Northern Province. The new species, Nucras margaritae sp. nov., is known only from its holotype. It is morphologically similar to N. ornata, from which it is separated by 620 airline km, but is deeply genetically divergent from all congeners and is sister to the clade comprising N. holubi, N. ornata, N. damarana and N. intertexta. At least five species of Nucras, four currently named, inhabit the greater eastern Zambezi River basin.